Design and Synthesis of Dipeptidomimetic Isocyanonaphthalene as Enhanced-Fluorescent Chemodosimeter for Sensing Mercury Ion and Living Cells - Wang, Xiao-Juan; Li, Gao-Wei; Cheng, Yi-Peng; Sun, Qiu-Ling; Hao, Yuan-Qiang; Wang, Chen-Hong; Liu, Lan-Tao (Frontiers in Chemistry, 2022)
A novel valine-based isocyanonaphthalene (NpI) was designed and synthesized by using an easy method and enabled the selective ﬂuorescence detection of Hg2+. The chemodosimeter can display an immediate turn-on fluorescence response (500-fold) towards target metal ion upon the Hg2+-mediated conversion of isocyano to amino within NpI. Based on this specific reaction, the fluorescence-enhancement probe revealed a high sensitivity toward Hg2+ over other common metal ions, and exhibited excellent aqueous solubility, good antijamming capability, high sensitivity (detection limit: 14.2 nM), and real-time detection. The response mechanism of NpI was supported by NMR spectroscopy, MS analysis and DFT theoretical calculation using various techniques. Moreover, dipeptidomimetic NpI probe was successfully applied to visualize intracellular Hg2+ in living cells and monitor Hg2+ in real water samples with good recoveries and small relative standard deviations.